Aging and Others' Pain Processing: Implications for Hospitalization. (31st August 2014) - Di Domenico, Alberto; Fairfield, Beth; Mammarella, Nicola
Abstract : Objectives . While self-pain perception has been widely investigated in aging, the perception as well as memory of pain in others has received little attention. Methods . The study was designed as a cross-sectional behavioral study in which a group of 41 younger and a group of 41 older adults evaluated a series of valenced and pain-related pictures and were later required to recall them. Results . We found that older adults judge the stimuli as being less intense compared to their younger counterparts. However, older adults remembered a larger number of pictures with individuals expressing pain compared to pictures with individuals who have neutral or positive facial expressions. Conclusions . Older adults may underestimate emotional intensity in others, but they seem to remember painful information in others as well as younger adults. These data are discussed in terms of theories of pain perception and implications for hospitalization.